2018
DOI: 10.29252/jrdms.3.4.38
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Correlation Between Vertical Facial Discrepancies and Cervical Vertebral Fusion

Abstract: Background and aim: To date, the possibility of any correlation between pathological problems associated with cervical vertebral fusion and long facial pattern has been limitedly assessed. The aim of the present study was to find the correlation between the risk of fusion in cervical vertebrae and long facial pattern in adults. Materials and methods: In the present cross-sectional study, 80 lateral cephalograms with proper density and contrast were selected. The vertical facial dimension was analyzed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, no previous study evaluated the effects of sildenafil and pentoxifylline on maxillofacial fractures. (42,(54)(55)(56) The current results revealed that pentoxifylline and sildenafil have positive effects on bone healing. Our findings regarding enhanced bone healing by sildenafil were in agreement with those of Yaman et al, Histing et al, and Çakir-Özkan et al (42,19,57) Aydin et al used pentoxifylline in a dosage similar to ours and showed that pentoxifylline enhances the formation of a hematoma, which is the first phase of bone healing.…”
Section: Discussionmentioning
confidence: 61%
“…However, no previous study evaluated the effects of sildenafil and pentoxifylline on maxillofacial fractures. (42,(54)(55)(56) The current results revealed that pentoxifylline and sildenafil have positive effects on bone healing. Our findings regarding enhanced bone healing by sildenafil were in agreement with those of Yaman et al, Histing et al, and Çakir-Özkan et al (42,19,57) Aydin et al used pentoxifylline in a dosage similar to ours and showed that pentoxifylline enhances the formation of a hematoma, which is the first phase of bone healing.…”
Section: Discussionmentioning
confidence: 61%